2017
DOI: 10.1002/eat.22687
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic suppression of binge‐like eating elicited by cyclic food restriction and frustrative‐nonreward stress in female rats

Abstract: Objective Because binge eating and emotional eating vary through the menstrual cycle in human females, we investigated cyclic changes in binge-like eating in female rats and their control by estrogens. Method Binge-like eating was elicited by three cycles of 4 days of food restriction and 4 days of free feeding followed by a single frustrative nonreward-stress episode (15 min visual and olfactory exposure to a familiar palatable food) immediately before presentation of the palatable food. Results Intact ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 62 publications
2
42
1
Order By: Relevance
“…On day 25, the final test day, each group was exposed or not to stress (15 min) (see Figure 1 for details). We found in a previous study that stress-induced BE in our model is not observed during the estrous phase (Alboni et al, 2017;Micioni Di Bonaventura, Lutz et al, 2017). In these conditions, the animal was able to see the cup and the palatable food itself and could smell its odor.…”
Section: Binge-eating Experimental Proceduresmentioning
confidence: 58%
“…On day 25, the final test day, each group was exposed or not to stress (15 min) (see Figure 1 for details). We found in a previous study that stress-induced BE in our model is not observed during the estrous phase (Alboni et al, 2017;Micioni Di Bonaventura, Lutz et al, 2017). In these conditions, the animal was able to see the cup and the palatable food itself and could smell its odor.…”
Section: Binge-eating Experimental Proceduresmentioning
confidence: 58%
“…The amygdala and BNST are brain regions anatomically and functionally connected (de Olmos & Heimer, 1999) and the amygdala is known to have CRF-containing projection to the BNST (Erb, Salmaso, Rodaros, & Stewart, 2001) and in particular CeA has emerged as an important area in the regulation of excessive consumption of palatable food (Blasio et al, 2013; de Olmos & Heimer, 1999; Iemolo et al, 2013; Micioni Di Bonaventura et al, 2017). The observation that blockade of CRF receptors in these brain areas completely reversed stress-induced binge eating in our model indicates a critical role of extrahypothalamic CRF systems.…”
Section: Discussionmentioning
confidence: 99%
“…This stress procedure has face validity as a model of the putative contributions of dieting and negative-valence states, to binge eating in humans (Association, 2013; Mathes, Brownley, Mo, & Bulik, 2009; Sanislow et al, 2010; Treasure, Claudino, & Zucker, 2010; Vannucci et al, 2015). Considering the high prevalence of binge eating in women (Hudson et al, 2007; Swanson et al, 2011), we used female rats, in which binge-like eating behavior varies across the estrus cycle (Alboni et al, 2017; Micioni Di Bonaventura et al, 2017), similarly to women (Culbert, Racine, & Klump, 2016; Edler, Lipson, & Keel, 2007; Klump et al, 2013; Schoofs, Chen, Braunig, Stamm, & Kruger, 2011) and this result increases the validity of the model that can be used in translational studies of the mechanism of binge eating behavior.…”
mentioning
confidence: 99%
“…Thus, an interpretation relevant to negative results in the exploration-based anxiety models is that the motor arousal may reflect food-seeking behavior. In this interpretation, the recent (2h) or otherwise expected availability (4h and 8h groups) of palatable food might supersede the anxiogenic-like plus-maze and defensive withdrawal environments, leading to food-seeking behavior despite the threat of open spaces (Micioni Di Bonaventura et al, 2017; Parylak et al, 2012). Such a result was seen in open-field conflict reinstatement tests(Dore et al, 2014; Teegarden & Bale, 2007).…”
Section: Discussionmentioning
confidence: 99%